The colonial origins of modern social thought French sociology and the overseas empire - Steinmetz, George 1957- (Princeton University Press, 2023)
A new history of French social thought that connects postwar sociology to colonialism and empireIn this provocative and original retelling of the history of French social thought, George Steinmetz places the history and development of modern French sociology in the context of the French empire after World War II. Connecting the rise of all the social sciences with efforts by France and other imperial powers to consolidate control over their crisis-ridden colonies, Steinmetz argues that colonial research represented a crucial core of the renascent academic discipline of sociology, especially between the late 1930s and the 1960s. Sociologists, who became favored partners of colonial governments, were asked to apply their expertise to such "social problems" as detribalization, urbanization, poverty, and labor migration.
Keywords: SOCIAL SCIENCE / Sociology / General; Sociology -- France -- History -- 20th century; Kolonialismus; Soziologische Theorie; Frankreich